2017
DOI: 10.1016/j.jtice.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Stagnation-point flow and heat transfer over an exponentially stretching/shrinking cylinder

Abstract: The stagnation-point boundary-layer flow and heat transfer over an exponentially stretching/shrinking cylinder is studied. The governing partial differential equations in cylindrical form are first transformed into ordinary differential equations which are then solved numerically using a shooting method. Results for the skin friction coefficient, local Nusselt number, velocity and temperature profiles are presented and discussed in detail. The effects of the stretching/shrinking parameter ɛ and the curvature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 37 publications
0
21
1
Order By: Relevance
“…Utilizing the following conversions [4,19,29] After applying above conversions, Eq. (8) is automatically satisfied and Eqs.…”
Section: Appropriate Conversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the following conversions [4,19,29] After applying above conversions, Eq. (8) is automatically satisfied and Eqs.…”
Section: Appropriate Conversionsmentioning
confidence: 99%
“…Moreover, he noted that intensifying values of slip velocity and thermal conductivity parameters decline the local Nusselt number. Markin et al [4] analyzed the flow and heat transfer analysis toward shrinking/stretching cylinder with stagnation point. Stretched flow of a Jeffrey liquid with the impact of MHD and chemical species was deliberated by Hayat et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…While, Rosali et al, [11] considered a rotating flow over an exponentially shrinking sheet with a suction effect. Merkin et al, [12] explored the stagnation-point flow and heat transfer over an exponentially stretching/shrinking cylinder and reported that as the curvature parameter increases, the heat transfer rate also increases and the solution for a shrinking cylinder is found to be non-unique.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Miklavčič et al [Miklavčič and Wang (2006)] were among the early researchers that investigated the flow over a shrinking sheet with the velocity moves towards the slit. Following this, the issue is becoming a common trend among the researchers which further emphasize the need to extend the problem of flow and heat transfer over a stretching/shrinking sheet to other different physical situations [Gupta and Gupta (1977); Bachok, Ishak and Pop (2010); Othman, Yacob, ; Nasir, Ishak and Pop (2017); Merkin, Najib, Bachok et al (2017); Jahan, Sakidin, Nazar et al (2018); Kamal, Zaimi, Ishak et al (2018)].…”
Section: Introductionmentioning
confidence: 99%